Perceptions and experiences of the menstrual cycle amongst elite adult and adolescent football players - Donnelly, J.; Valentin, S.; Easton, C.; White, A.; Forrest (Née Whyte), L. J. (Science and Medicine in Football, 2026)
The purpose of this study was to investigate players` experiences and perceptions of the menstrual cycle (MC) and the perceived impact on performance. Female elite adult (n = 31, age 24.6 ± 5.1 years) and adolescent (n = 65, age 15.0 ± 1.1 years) players completed an online questionnaire consisting of quantitative and qualitative questions. MC symptoms were experienced by 90.1% naturally menstruating participants (86.9% adolescents and 93.6% adults (x2 = 1.53, df = 2, p = 0.47, n = 92)), and 78.3% adolescents perceived their MC impacts performance, compared to 96.4% adults (x2 = 4.54, df = 1, p = 0.033, n = 74). Physical symptoms, psychological symptoms and energy levels were cited as key reasons for the MC negatively impacting performance. Challenges in communicating MC experiences were reported by 44.92% (n = 23) adolescents compared to 20.0% (n = 6) adults (x2 = 7.29, df = 2, p = 0.026, n = 82), with a perceived lack of knowledge, ability to relate and awkwardness cited as key reasons. Football players report wellbeing and performance impacts due to their MC, highlighting the need for individual understanding and support. Furthermore, understanding the experiences of adolescents enables the development of targeted support structures that equip them with tools to manage and communicate about their MC, and hopefully preventing issues as they become senior players.